Kontribusi Badan Kesatuan Bangsa dan Politik (KESBANGPOL) Provinsi Sumatera Barat dalam Upaya Pencegahan Korupsi - Muthia Julian Zahra; Irma Cahyani; Raudhatul Natasya Annur; Kencana Firjatullah Kusuma; Yulia Hanoselina; Rahmadhona Fitri Helmi (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
Kesbangpol West Sumatra Province has a strategic role in preventing corruption, which is still a serious challenge in Indonesia. This research aims to evaluate the contribution of Kesbangpol in preventing corruption through theoretical and practical approaches. This study adopts Weberian bureaucratic theory, good governance, anti-corruption, and state administration ethics as a conceptual basis. The research uses qualitative methods through interviews, direct observation and documentation studies. The research results show that Kesbangpol has implemented various strategic steps such as anti-corruption education programs, strengthening transparency, as well as preventive, repressive and detective approaches. Educational programs include political education and national insight aimed at building community integrity, especially the younger generation. Transparency strategies include wealth reporting, digital-based financial management, and online attendance to reduce the potential for abuse of authority. Harmony between Weberian bureaucratic theory, good governance, and anti-corruption approaches has proven effective in forming an efficient, accountable and transparent bureaucratic system. However, technical challenges and lack of intensive supervision remain obstacles to policy implementation. This research has the implication that the application of technology and strengthening internal supervision can strengthen the role of Kesbangpol in creating a clean and stable government.